The Impact of the Dimensions and Consequences of Human Resource Management Development on the Performance Gap in the Social Security Organization - Ebrahim Javaheri , Mohammad; Rousta , Alireza; Ashrafi, Azadeh (Future of Work and Digital Management Journal, 2024)
The present study examines the impact of the dimensions and consequences of human resource management (HRM) development on the performance gap in the Social Security Organization. The research is applied in terms of purpose and descriptive–survey and causal in nature. The information was collected through a library method, and the required data were obtained by note-taking from books, articles, theses, and other relevant sources. The statistical population consisted of employees and managers of the Social Security Organization. The sampling method was simple random sampling, and due to the unknown size of the population, the sample size was determined to be 384 individuals. Data collection in the field was carried out using a researcher-made questionnaire. Data were analyzed using descriptive statistics (mean and standard deviation), inferential statistics, and structural equation modeling with the use of SPSS 26 and AMOS 24 software. The findings indicated that both the dimensions of HRM development and its consequences have significant effects on the factors influencing the performance gap, including human resources, organizational structure and processes, external environment, and managerial factors. The results further revealed that the dimensions and consequences of HRM development can play a significant role in reducing the performance gap within the Social Security Organization.